Giving Meaning to Action and Research: Notes on the ‘One Health’ Approach from a Sociological Perspective - Balduzzi, Giacomo; Favretto, Anna Rosa (Development (Society for International Development), 2023)
The One Health (OH) approach emphasizes the need to tackle the challenges of human, animal and ecosystem health using a more integrated approach. Since the mid-2000s and even more since the outbreak of the COVID-19 pandemic, public health scholars and policymakers have been paying an increasing attention to the One Health approach. The authors retrace the different reconstructions on the origins and meanings of the One Health approach also by referring to a case study jointly conducted by sociologists and veterinary epidemiologists in the context of dairy cattle farms located in the provinces of Turin and Cuneo. According to Beck (1992), in risk societies, the division of labour between science, politics and economics breaks apart and must be renegotiated. Moreover, according to Pierre Bourdieu, One Health is understandable, in sociological terms, as a social field, that is arenas where actors’ relations stem from the different positions in the field and from their different dispositions ( habitus ). Dominant groups are also recognizable. In this perspective OH takes shape as a peculiar form of real (or possible) utopia: that of using the network of connections by which we grasp the risks to formulate an integrated strategy able at promoting health from a global and systemic standpoint and preventing the potential for irreversible destruction.